THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND JOB SATISFACTION TOWARDS ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE - Maswani; Syah T.Y.R.; Anindita R. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
The purpose of the study is to analyze the relationship between organizational culture, job satisfaction, organizational commitment and employee performance in the Government. In this study the population was 135 employees in the work unit of the Secretary General of the Ministry of Defense in 2018, and in this study, all of them acted as respondents. The data analysis technique uses the Structural Equation Modeling (SEM) analysis method. The results of the study show that organizational culture and job satisfaction have a positive effect on organizational commitment, so good organizational culture and job satisfaction can increase organizational commitment. Organizational commitment has a positive effect on employee performance, the higher organizational commitment can improve employee performance. organizational culture and job satisfaction have a negative influence on employee performance. This proves that organizational culture and decreased job satisfaction cannot affect employee performance in carrying out the main tasks and functions of the organization.